Scope and applications of nanotechnology for wheat production: A review of recent advances - Jasrotia, Poonam; Kashyap, Prem Lal; Bhardwaj, Ajay Kumar; Kumar, Sudheer; Singh, Gyanendra Pratap (Journal of Cereal Research, 2018)
Wheat (Triticum aestivum) is main staple food grain crop, grown in a range of environments over an area of 221.6 million hectares (M ha) with an annual production likely to reach more than 750.4 million metric tons in 2016-17 (Foreign Agricultural Service, USDA, 2018). Despite this significant growth, the world population in some parts is still facing hunger crisis due to insufficient availability of food grains. To meet the future food demands imposed by an overwhelming increasing population which is expected to reach nine billion in 2050, the world wheat production must continue to increase by 2% annually. This challenge of increasing wheat production is daunting as the wheat cropping system at present is constrained by climatic fluctuations, poor soil health andhas increased the risk of an epidemic outbreak of diseases and insect-pests. To address these challenges, innovative technologies with a potential of increasing the sustainability of the present day cropping systems are required to be introduced in modern agriculture. Among these technological advancements, nanotechnology is gathering significant contemplations due to its wide spectrum applications in agriculture and allied sectors. It has a wider application in the field of crop production, food security, sustainability and climate change and is being utilized for developing several precise tool setts like  nanofertilizer, nanopesticide, nanoherbicide, nanosensor and smart delivery systems for controlled and sustained release of agrochemicals. Recent research evidence indicated that intervention of nanotechnology in wheat farming is still in its early stages, although have bright prospects for efficient nutrient utilization through nanoformulations of fertilizers, breaching yield barriers through bionanotechnology, surveillance, and management of pests and diseases and development of new-generation pesticides etc. Doi.org/10.25174/2249-4065/2018/76672